2016
DOI: 10.4103/1947-2714.175188
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T in patients with traumatic chest injuries with and without cardiac involvement: Insights from an observational study

Abstract: Background:Serum troponin T (TnT) is a common marker of myocardial injury. However, its implication in the absence of clinical evidence of cardiac reason is not well established.Aims:The aim of this study was to identify the implications of positive TnT in traumatic chest injury (TCI) patients regardless of the cardiac involvement.Materials and Methods:We conducted a retrospective analysis of all TCI patients admitted to level 1 trauma center between 2008 and 2011. Patients who underwent TnT testing were divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…Other tests, such as cardiac biomarkers (CBMs), have been proposed for the diagnosis of BCRs. However, CBMs also have been shown to lack specificity, as Mahmood et al observed elevated CBMs in 20% of blunt chest trauma, even in the absence of cardiac involvement [60]. Recently, several studies, including a meta-analysis [54], have suggested the combined use of ECG and CBMs to rule out BCIs and/or monitor its progression [15].…”
Section: Discussionmentioning
confidence: 99%
“…Other tests, such as cardiac biomarkers (CBMs), have been proposed for the diagnosis of BCRs. However, CBMs also have been shown to lack specificity, as Mahmood et al observed elevated CBMs in 20% of blunt chest trauma, even in the absence of cardiac involvement [60]. Recently, several studies, including a meta-analysis [54], have suggested the combined use of ECG and CBMs to rule out BCIs and/or monitor its progression [15].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors proposed cardiac troponin level measurements as a screening test prior to echocardiographic workup and data suggests that severity of cardiac arrhythmias correlates with cardiac troponin levels [17, 23]. Moreover, even in the absence of clinical evidence of cardiac involvement, troponin leaks may be associated with worse outcomes in patients with blunt chest trauma [13]. Despite these insights, it is believed that cardiac contusions and associated structural cardiac injuries remain underdiagnosed [24].…”
Section: Discussionmentioning
confidence: 99%
“…Además, en los pacientes que presentaban trauma cardiaco cerrado, la troponina a las 6 horas del trauma aumentó (mediana de 1,78 µg/L), en comparación con una de 0,1 µg/L en quienes no lo sufrieron; no obstante, dado el escaso número de pacientes (n=6), no se pudo establecer una significación estadística. En el presente estudio, no se evaluó la troponina T, con gran especificidad y valor pronóstico en la morbimortalidad en casos de trauma cardiaco 24 .…”
Section: Discussionunclassified